학습 튜터링 프로그램이 대인관계, 자기주도적 학습력과 학업적 자기효능감에 미치는 효과 - 곽정숙(Jung-Suk Kwag); 우승희(Seung-Hee Woo) (한국콘텐츠학회 논문지, 18(7), 2018)
The purpose of this study was to examine the influence of an academic tutoring program on interpersonal relationships, self- directed learning capability and academic self-efficacy. The research question posed in this study was whether an academic tutoring program would affect interpersonal relationships, self-directed learning capability and academic self-efficacy. To address the research question, a self-administered survey was conducted to gather data on 214 students who participated in an academic tutoring program during a semester from September 4 to November 10, 2017. The findings of the study were as follows: After their participation in the tutoring program, there was a little decrease in self-directed learning capability and personal learning orientation, and they made progress in interpersonal relationships and academic self-efficacy. By gender, there was the greatest improvement in interpersonal relationships as well after their participation in the tutoring program. By academic year and motivation for participation, they showed the best improvement in interpersonal relationships as well, followed by academic self-efficacy. In other words, it could be said that the parts which the tutoring program brought about the biggest change to and worked best on were interpersonal relationships and academic self-efficacy. In conclusion, the improvement of interpersonal relationships and academic self-efficacy could boost not only the school adjustment of students but their academic levels and then eventually prevent them from dropping out. Therefore this program seems to be one of outstanding learning programs that could make a contribution to the stable management and qualitative competitiveness of universities. 본 연구는 학습 튜터링 프로그램이 대인관계와 주도적 학습력 및 학업적 자기효능감에 미치는 영향을 분석하는데 그 목적이 있다. 연구 목적에 따라 설정한 연구 문제는 학습 튜터링 프로그램이 대인관계, 주도적 학습력, 학업적 자기효능감에 영향을 미치는가를 알아보기 위해 프로그램 실시 전, 후 대인관계, 자기주도 학습력, 학업적 자기효능감에 변화가 있는가를 살펴보고자, 2017년 9월 18일부터 11월 17일까지 한 학기동안 학습 튜터링 프로그램에 참여한 재학생 214명을 대상으로 자기기입식 설문지법을 통해 자료를 수집하였으며 다음과 같은 결론을 얻었다. 튜터링 프로그램 참여 후 자기주도 학습력과 개인학습성향은 튜터링 프로그램 참여 전보다 다소 감소됨을 보였고, 대인관계와 학업적 자기효능감은 향상됨을 보였다. 성별에 따라서도 튜터링 프로그램 전, 후 가장 크게 향상된 부분은 대인관계이고, 학년과 참여 동기에서도 가장 향상된 부분은 대인관계이었으며, 그 다음으로는 학업적 자기효능감인 것으로 나타났다. 다시 말하면 튜터링 프로그램을 시행하여 가장 크게 변화되고, 효과를 나타내는 부분이 대인관계와 학업적 자기효능감이라 말할 수 있는 결과를 보였다. 결국, 대인관계 및 학업적 자기효능감의 향상은 학생들의 학교적응뿐만 아니라 학업수준까지 향상시켜 결국에는 중도탈락을 예방하여 대학 기관의 안정적 운영과 질적 경쟁력 제고에 기여할 수 있는 우수한 학습 프로그램이라 판단한다.